Synthesis of Inorganic Nanomaterials : Advances and Key Technologies. - Bhagyaraj, Sneha Mohan; Oluwafemi, Samuel Oluwatobi; Kalarikkal, Nandakumar; Thomas, Sabu (Elsevier Ltd. : Woodhead Publishing, 2018)
Synthesis of Inorganic Nanomaterials: Advances and Key Technologies discusses the latest advancements in the synthesis of various types of nanomaterials. The book's main objective is to provide a comprehensive review regarding the latest advances in synthesis protocols that includes up-to-date data records on the synthesis of all kinds of inorganic nanostructures using various physical and chemical methods. The synthesis of all important nanomaterials, such as carbon nanostructures, Core-shell Quantum dots, Metal and metal oxide nanostructures, Nanoferrites, polymer nanostructures, nanofibers, and smart nanomaterials are discussed, making this a one-stop reference resource on research accomplishments in this area. Leading researchers from industry, academia, government and private research institutions across the globe have contributed to the book. Academics, researchers, scientists, engineers and students working in the field of polymer nanocomposites will benefit from its solutions for material problems.- Resumé vydavatel
Keywords: nanomateriály; anorganické sloučeniny; chemické syntézy; nanomaterials; inorganic compounds; synthesis; sborníky; elektronické knihy; papers of several authors; electronic books